Оценка рисков технико-экономической защищенности на этапах жизненного цикла объектов недвижимости - Кущенко, Игорь Владимирович; Бочарова, Елена Анатольевна (Недвижимость: экономика, управление, 2024)
Введение. Представлен инновационный подход к устойчивому развитию объектов недвижимости на основе комплексного анализа требований ресурсосбережения, технико-экономической защиты и безопасной эксплуатации. Выявлены недостатки действующих норм проектирования мер защиты от коррозии, не позволяющие производить моделирование расчета стоимости жизненного цикла (ЖЦ). Показана необходимость расширения расчетно-аналитических индикаторов экспертизы проектных решений с целью предотвращения негативных последствий при коррозионном разрушении. Материалы и методы. Объект исследования представляет систему регламентного управления, для которой разработаны алгоритмы принятия эффективных решений строительных проектов по защите от коррозии. Предложена методика резервирования технико-экономической защищенности на базе расчетных моделей качества, надежности и безопасности конструкций и сооружений. Функциональное и временнόе резервирование устойчивости к агрессивным воздействиям осуществляется с учетом требований к эксплуатации и безопасности стандарта ИСО/ТК 267 Фасилити менеджмент (ФМ). Целостное восприятие критериев технико-экономической защиты достигается с помощью индикаторов экспертизы проектных решений и регламента ЖЦ для заданного уровня коррозионной опасности (KI – KV) или защищенности (ZI – ZIV). Результаты. Апробация принципов и условий регламентного резервирования мер технико-экономической защиты выполнена путем постановки прямой и обратной задач живучести. Программа определительных испытаний включала мониторинг, риск-диагностику и управление индикаторами расчета стоимости ЖЦ. Оценка рисков осуществлена на основе метода HAZOP (Hazard and Operability Study). Предложенный подход обеспечивает сценарный анализ возможностей и идентификацию угроз применения новых материалов и технологий согласно положениям концепции «бережливого хозяйствования» Lean Six Sigma. Introduction. An innovative approach to the sustainable development of real estate objects based on a comprehensive analysis of the requirements of resource conservation, technical and economic protection and safe operation is presented. The shortcomings of the current standards for the design of corrosion protection measures are identified, which do not allow modelling the calculation of the life cycle cost (LC). It is shown that it is necessary to expand the calculation and analytical indicators of the expertise of design solutions in order to prevent negative consequences in case of corrosion failure. Materials and methods. The object of the study is a regulatory management system for which algorithms for making effective decisions on corrosion protection construction projects are developed. A technique for reserving technical and economic protection based on computational models of quality, reliability and safety of structures and structures is proposed. Functional and temporary redundancy of resistance to aggressive influences is carried out taking into account the requirements for operation and safety of the ISO/TC 267 Facility Management (FM) standard. A holistic perception of the criteria of technical and economic protection is achieved with the help of indicators of the expertise of design solutions and the regulations of the housing and communal services for a given level of corrosion hazard (KI – KV) or protection (ZI – ZIV). Results. The approbation of the principles and conditions of the regulatory reservation of technical and economic protection measures was carried out by setting direct and inverse survivability tasks. The programme of definitive tests included monitoring, risk diagnostics and management of indicators for calculating the cost of housing and communal services. The risk assessment was carried out on the basis of the HAZOP (Hazard and Operability Study) method. The proposed approach provides a scenario analysis of the possibilities and identification of threats to the use of new materials and technologies in accordance with the provisions of the Lean Six Sigma concept of “lean management”. Conclusions. The theoretical and experimental substantiation of the principles of the regulatory management system for corrosion protection and survivability of real estate objects contributes to the promotion of digital technologies and platform solutions for technical and economic protection based on target indicators of quality, reliability and safety of structures and structures.